Impact of leadership styles on employees' performance with moderating role of positive psychological capital. (4th July 2021) - Baig, Sajjad Ahmad; Iqbal, Saher; Abrar, Muhammad; Baig, Irfan Ahmad; Amjad, Fiza; Zia-ur-Rehman, Muhammad; Awan, Muhammad Usman
Abstract : The study aimed to investigate the most effective leadership style that enhances the employees' performance at the workplace and also evaluate the impact of leadership styles (Laissez-faire leadership, Transformational leadership, Transactional leadership, ) on employees' performance in the textile sector of Pakistan. The study explored the moderating role of Positive psychological capital to examine the relationship between leadership styles and employee performance. A quantitative research technique was used, and Data were collected from the lower to middle-level manager of the textile sector. The findings of this study showed that laissez-faire leadership has a significant but negative impact on employee's performance; however the moderating effect of psychological capital has made this relationship negatively significant. Transformational leadership has a significant impact on employee performance. Moreover, transactional leadership has an insignificant effect on employee performance by adding psychological capital as a moderator; this relationship has become positively significant. The textile organisations of Pakistan have been facing many challenges, including lower employee satisfaction and performance. Through the transformational leadership styles, the organisations may improve the employees' performance as the study supported this argument. The results would have practical implications for policymakers, employees, and management. The study has contributed in developing the relationship between the leadership styles and employee performance by adding an unexplored moderator, which is – Positive psychological capital – in an ignored social setting of the textile organisation.